2009
DOI: 10.1136/gut.2008.171124
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human hepassocin stimulates proliferation of hepatocytes in vivo and improves survival in rats with fulminant hepatic failure

Abstract: HPS is a hepatic growth factor which can accelerate hepatocyte proliferation in vivo and protect against liver injury. These data point to the potential interest of HPS in the treatment of fulminant hepatic failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 27 publications
5
88
0
Order By: Relevance
“…Research has indicated that FGL1 exerts multiple hepatic protective functions by promoting hepatocyte proliferation and decreasing the rate of apoptosis. A previous study indicated that administration of FGL1 to animals following D-Gal treatment significantly reversed liver injury by promoting hepatocyte proliferation and reducing liver apoptosis, while knockdown of endogenous FGL1 expression exacerbated liver injury (22,23). Concurrent with these results, the present study indicated that the level of FGL1 was enhanced 72 h following the induction of liver injury, indicating that FGL1 was activated upon induction of spontaneous liver regeneration.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Research has indicated that FGL1 exerts multiple hepatic protective functions by promoting hepatocyte proliferation and decreasing the rate of apoptosis. A previous study indicated that administration of FGL1 to animals following D-Gal treatment significantly reversed liver injury by promoting hepatocyte proliferation and reducing liver apoptosis, while knockdown of endogenous FGL1 expression exacerbated liver injury (22,23). Concurrent with these results, the present study indicated that the level of FGL1 was enhanced 72 h following the induction of liver injury, indicating that FGL1 was activated upon induction of spontaneous liver regeneration.…”
Section: Discussionsupporting
confidence: 72%
“…FGL1 (also termed FREP1 or hepassocin) is a protein secreted by hepatocytes, which is a member of the fibrinogen family (20). Studies have shown that FGL1 is implicated in liver injury as a mitogenic growth factor and may facilitate damaged liver tissue regeneration and downregulate the expression of proapoptotic factors (21)(22)(23). In the present study, it was hypothesized that intravenous transplantation of BMSCs may increase the expression of FGL1 in the injured rat liver and rescue the liver following acute injury.…”
Section: Introductionmentioning
confidence: 90%
“…To determine whether HPS affected proliferation of hepatoma cells, four hepatoma cell lines were treated with rhHPS, and the growth of these cells were not affected (data not shown), which agreed with the previous studies [Hara and Yoshimura, 2001;Li et al, 2010], suggesting a different mechanism of HPS in the regulation HCC cell growth. To confirm this hypothesis, we transfected HPS expression vector (pcDNA-HPS) or HPS mutant (pcDNA-DN22) into HepG2 cells, and the growth of G418-resistant clones were measured.…”
Section: Hps Inhibits Proliferation Of Hcc Cells Through An Intracrinsupporting
confidence: 83%
“…After 70% hepatectomy of mouse liver, HPS was induced at 2 h and the second peak arrived at 24 h. The expression of HPS maintained high until 72 h and declined to the basal level thereafter. These results indicated that HPS might function as a regulator of hepatocyte growth and be involved in liver regeneration [Li et al, 2010]. On the other hand, studies also have revealed that HPS was associated with progression of liver tumors.…”
mentioning
confidence: 89%
See 1 more Smart Citation